George Eliot's dialogue with John Milton - Nardo, Anna K., 1947- (University of Missouri Press, 2003)
In George Eliot's Dialogue with John Milton, Anna K. Nardo details how Eliot reimagined Milton's life and art to write epic novels for an age of unbelief. Nardo demonstrates that Eliot directly engaged Milton's poetry, prose, and the well-known legends of his life--transposing, reframing, regendering, and thus testing both the stories told about Milton and the stories Milton told. --From publisher's description.